Determinants of financial inclusion in households in Peru - Quispe Mamani, Julio Cesar; Aguilar Pinto, Santotomas Licimaco; Calcina Álvarez, Dominga Asunción; Quispe Layme, Marleny; Gutierrez Toledo, Guino Percy; Condori Condori, Gina Tamara; Vargas Espinoza, Luis; Quispe Layme, Wilian; Marca Maquera, Hugo Rubén; Rosado Chávez, Charles Arturo (Frontiers in Sociology, 2024)
The issue of financial inclusion that considers access and use of quality financial services by household members and by different types of companies in the world, which allows us to reach the opportunities that the globalized world offers us. The objective of the research was to identify the socioeconomic factors that determine the inclusion of households in the financial system in Peru in the period 2021. The quantitative approach was considered, non-experimental with a descriptive and correlational design, where the amount of 81,441 data obtained from the National Household Survey (ENAHO) of the National Institute of Statistics and Informatics was used, applying a Logit-binomial regression. It was determined that 47.02% of households are included in the financial system; 61.93% of those surveyed have their residence in the urban area; on average, respondents have incomplete secondary education; the age of the respondents on average was 25 to 44 years; the average economic income of the household is less than 251 per month; 72.18% are represented by men as heads of the household and the rest by women; most of the respondents have a cohabiting marital status; the social conditions show that 23.82% are in the group of being poor; and in the case of property title, the majority of households do not have property title. The determinants of financial inclusion in Peruvian households for 2021 were; the area of residence, educational level, age of the respondent, economic income, gender of the respondent, marital status, social status and property title.